The restricted IgG1 antibody response to maedi visna virus is seen following infection but not following immunization with recombinant gag protein. - Bird, P (1995)
Maedi-visna (MVV) is a retrovirus of the subfamily lentivirinae which includes HIV, simian immunodeficiency virus (SIV) and feline immunodeficiency virus (FIV). Infection of its natural host, the sheep, does not cause overt immunodeficiency, but rather a chronic inflammatory disease. However, subtle immunological changes following infection have been reported including a sheep IgG1 subclass-restricted MVV-neutralizing antibody. Here we demonstrate by Western blotting that there is no IgG2 serum antibody response to any MVV antigen after MVV infection, in contrast to infection with the parapox virus Orf, when serum IgG2 anti-Orf antibody is readily detected. By ELISA, the IgG1 antibody titres to Orf are higher than to MVV, but the minimum MVV serum antibody IgG1/IgG2 ratio is significantly raised compared with that for Orf virus antibody in the same sheep, indicating that the IgG2 defect in MVV infection cannot be accounted for by differences in the sensitivity of the Orf and MVV ELISA. Serum IgG2 anti-MVV gag p. 25 can be detected in both normal and MVV-infected sheep following immunization with purified recombinant MVV gag p 25 protein in Freund's complete adjuvant. The failure to make an IgG2 MVV-specific antibody indicates that immunological dysfunction can arise with macrophage tropic lentiviruses, and it may aid viral persistence.